Who counts? : 100 sheep, 10 coins, and 2 sons - Levine, Amy-Jill, 1956-; Sasso, Sandy Eisenberg (Louisville, KY : Westminster John Knox Press, 2017)
Who Counts? is a creative retelling of three popular parables: the lost sheep, the lost coin, and the prodigal son. As young readers count to help the characters find what's missing, Who Counts? teaches that every one of us counts in God's eyes and that everyone should feel counted.
Keywords: Jesus Christ -- Parables -- Juvenile literature; Self-esteem -- Religious aspects -- Christianity -- Juvenile literature; Bible stories -- N.T.; Parables; JUVENILE FICTION -- Concepts -- Counting & Numbers; JUVENILE FICTION -- Religious -- Christian; Parables, Biblical; Self-esteem -- Religious aspects -- Christianity